BUILDING HUMAN CAPITAL MANAGEMENT FOR DEFENCE FORCES LECTURERS AT SESKOAL THROUGH CODE AND COMMISSION OF ETHICS - Sulistiyanto Sulistiyanto; Syarifudin Tippe; Dedi Purwana; Rachma Fitriati (AIBPM Publisher, 2019)
Human capital management (HCM) is a new development of human resource management. The definition of human capital emphasizes the notion that humans are one of the main capitals in an organization or company with infinite value and amount, manageable in a process, and in turn producing more values for the organization. This study aims to offer an idea in building human capital management for Defense Forces Lecturers at Naval Command and Staf College (NCSC/SESKOAL) through formulating rules about the Code of Ethics of Defense Forces Lecturers and the establishment of the Commission of Ethics at SESKOAL. This study uses soft systems methodology-based action research. The findings of this study indicate that these rules can improve the quality and motivation of lecturers at SESKOAL in Indonesian National Defence Forces (INDF/TNI) towards a world-class military college.